Conceptual framework for personal recovery in mental health among children and adolescents: a systematic review and narrative synthesis protocol. Issue 8 (15th August 2019) - Ballesteros-Urpi, Anna; Slade, Mike; Manley, David; Pardo-Hernandez, Hector
Abstract : Introduction: Personal recovery has been defined as 'a profound personal and unique process for the individual to change their attitudes, values, feelings, goals, abilities and roles in order to achieve a satisfactory, hopeful and productive way of life, with the possible limitations of the illness'. However, research on personal recovery has focused almost exclusively on adults. This project aims to systematically review the available literature on definitions of personal recovery among children and adolescents with mental health conditions and to undertake a narrative synthesis to develop a conceptual framework of recovery. Methods and analysis: Systematic review and narrative synthesis consisting (1) searching scientific literature databases, (2) handsearching, (3) citation tracking, (4) grey literature searching, (5) web-based searching and expert consultation. We will include qualitative and quantitative studies or systematic reviews providing a definition, theoretical or conceptual framework, domains or dimensions of personal recovery among eligible participants. The study will follow standard systematic review methodology for study selection and data extraction. We will assess quality of the evidence using tools appropriate for each study design. We will develop a new conceptual framework using a modified narrative synthesis approach, as follows: (1) describing eligible studies and conducting a preliminary synthesis, (2) determining relationships within and between studies and (3) determining the robustness of the synthesis. Ethics and dissemination: We obtained a waiver of approval from our local Research Ethics Committee. Results will be disseminated via publications in international peer-reviewed journals and conference proceedings. This study will result in a theoretical framework that is based on an exhaustive review of the literature and the input of experts in the field of recovery. We expect that this framework will foster a better understanding of the stages and processes of recovery in children and adolescents with mental health conditions. PROSPERO registration number: CRD42018064087.